Escitalopram induced syndrome of inappropriate antidiuretic hormone in elderly: an interesting scenario - Sharma, Tarun; Sharma, Aradhna; Kaistha, Madhvi; Kaur, Rajneet (International Journal of Basic & Clinical Pharmacology, 2016)
Selective serotonin reuptake inhibitors (SSRI) are the first line drugs used in the treatment of endogenous depression. Though clinically well tolerated in elderly, hyponatremia is one of the recognized side effects and its pathophysiology may be linked to syndrome of inappropriate antidiuretic hormone (SIADH). This side effect of SSRIs is a serious one since it can cause death also, if not diagnosed at the onset. This is an interesting case of an elderly patient who developed hyponatremia which further related to SIADH induced by escitalopram, an SSRI. The patient had symptomatic improvement in depression within one month but symptoms of hyponatremia appeared and then deteriorated again. Severe hyponatremia, serum hypo-osmolality, urine osmolality, and measurable levels of plasma antidiuretic hormone suggested SIADH. The hyponatremia improved after stoppage of the offending drug along with conservative medical therapy in hospital. Clinicians should be aware of this uncommon but significant side effect of escitalopram and monitor high-risk patients for the development of SIADH.